Rationalization of Physicochemical and Structural Requirement of Some Substituted 5-(Biphenyl-4-ylmethyl)Pyrazole as Angiotensin II Receptor Antagonist: A QSAR Approach: QSAR study of 5-(Biphenyl-4-ylmethyl)Pyrazole - Anurekha Jain,; Sumit Ratnawat,; S.C. Chaturvedi, (Iranian Journal of Pharmaceutical Sciences, 2010)
A series of angiotensin II (A II) receptor antagonist of some substituted 5-(biphenyl-4-ylmethyl) pyrazole were subjected to QSAR analysis using Hansch and Fujita-Ban model, by using combination of thermodynamic, electronic, spatial descriptor and presence or absence of substituent respectively. Several QSAR model were obtained using stepwise regression analysis. Two models from both the method were selected on the basis of the statistical value that shows good significance with AII antagonistic activity. The best QSAR models further validated by leave one out cross validation method. The studies have help to ascertain the role of different substituent in explaining the observed antagonistic activity of this analogue. From Fujita-Ban model, it is predicted that butane and propane at position 1, COOH at position 4 are essential for activity. Group like CH2CF3 at position 1 and COOH in place of tetrazole at R3 position contribute negative to the biological activity. In Hansch model it is predicted that molar refractivity at the 1 and 3 position shows positive contribution to the biological activity. Field effect at position 4 also shows positives contribution to the biological activity. Hydrogen donar at position R3 and field effect at position 1 contributes negatively to the biological activity.